Exploring the trends of retail formats in India - A study of shopping malls - Gupta, S. L.; Kaur, Tripat (Indian Journal of Marketing, 2007)
The study puts focus on how retailers are designing organized retail formats to keep pace with the changing moods of the shoppers. These organized retail formats are at a paradigm shift in India and the need of an hour is a place where the consumers are seeking the convenience of one -stop shopping which can be catered by none other but Malls. In past few years there has been a shift in India from individual retail outlets owned separately and managed distinctively to professionally managed retailing. Things changed primarily because of rising expectations of Indian Consumers and Corporate in turn responded quickly to the needs of consumers. This paper assesses the recent trends in the changing scenario of distribution in India with specific reference to the growth of large retail stores and their private labels. It dwells deeper into the performance of private labels and its implications to national brands in their marketing strategy. The retail formats commonly analyzed are stores located in the malls. The Apparel market is growing rapidly and changes are occurring across the industry, which has positioned itself as attractive destination. The study addresses how factors within and outside the stores affect store-level shopping decision. (This design was used to produce a picture of factors retailers consider important for shoppers while purchasing apparel with mass merchandise). Preference for certain retailer attributes differs by shopper and these preferences are reflected in store choice Therefore, several retailers’ attributes as reasons for store patronage. A questionnaire was designed to investigate store patronage relative to importance and perception of selected attribute of the stores. The data was collected from retailers. Respondents were asked to describe their perception of store on the basis of various attributes. These attributes were then treated as variables/indicators in the study. The six main indicators on the basis of which retailers decide to go for specific type of retail format consisted of Price, Sales Personnel, Quality of Merchandise, Assortment of Merchandise, Advertising, Services and other Convenience Services. The data was collected from 100 retailers.